1998
DOI: 10.3109/00207459809003336
|View full text |Cite
|
Sign up to set email alerts
|

Utiility of the Maternal Perinatal Scale (MPS) in Distinguishing Normal from Learning Disabled Children

Abstract: This study examined perinatal complications and risk factors as predictors of learning disabilities in schoolaged children. Specifically, the Maternal Perinatal Scale (MPS) was used to distinguish between normal children and those classified as learning disabled (LD) by their school system. One hundred and eight participants, 54 in each classification, were selected from a small Midwestern area. A stepwise discriminant analysis demonstrated that all four factors of the MPS contribute significantly to the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…On the other hand, some studies have reported learning disabilities (LDs) in children exposed to perinatal risks. These risk factors would explain the neuropsychological disorders and brain dysfunctions associated with impairments in visual perception and language skills (Hill, Cawthorne, & Dean, ; Xue, ). Colletti () found that 31% of children with LDs had a history of birth problems, and another 30% had suffered anoxia, circulatory disturbances, or respiratory distress that could explain the typical cognitive difficulties found in children with LDs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies have reported learning disabilities (LDs) in children exposed to perinatal risks. These risk factors would explain the neuropsychological disorders and brain dysfunctions associated with impairments in visual perception and language skills (Hill, Cawthorne, & Dean, ; Xue, ). Colletti () found that 31% of children with LDs had a history of birth problems, and another 30% had suffered anoxia, circulatory disturbances, or respiratory distress that could explain the typical cognitive difficulties found in children with LDs.…”
Section: Introductionmentioning
confidence: 99%
“…Results of our study are consistent with the study of Resnick et al [27], who suggests that perinatal and sociodemographic factors are both associated with specific learning disabilities. Other researchers also emphasize a great influence of perinatal risk factors on poor school achievement [5,15,28].…”
Section: Discussionmentioning
confidence: 97%
“…Es evidente que los resultados de un embarazo de riesgo pueden conllevar alteraciones físicas, sean por trastornos congénitos o por complicaciones en el desarrollo del embarazo y/o parto (Koniak y Turner, 2001). Se observan, a su vez, repercusiones psicopatológicas diversas (Arseneault, Tremblay, Boulerie y Saucier, 2002), trastornos psiquiátricos (Eaton et al, 2001), déficits cognitivos (Bratchelor, Dean, Gray y Wenck, 1989), alteraciones comportamentales (Weissman, Warner, Wickramaratne y Kandel, 1999), trastornos generalizados del desarrollo (Wilkerson et al, 2002), dificultades de aprendizaje (Hill, Cawthorne y Dean, 1998) y alteraciones neuropsicológicas (Jones et al, 1998).…”
Section: Teorías Y Modelo Patogénicosunclassified